Dark triad personality traits are associated with decreased grey matter volumes in ‘social brain’ structures - Myznikov, Artem; Korotkov, Alexander; Zheltyakova, Maya; Kiselev, Vladimir; Masharipov, Ruslan; Bursov, Kirill; Yagmurov, Orazmurad; Votinov, Mikhail; Cherednichenko, Denis; Didur, Michael; Kireev, Maxim (Frontiers in Psychology, 2024)
Personality traits and the degree of their prominence determine various aspects of social interactions. Some of the most socially relevant traits constitute the Dark Triadnarcissism, psychopathy, and Machiavellianismassociated with antisocial behavior, disregard for moral norms, and a tendency to manipulation. Sufficient data point at the existence of Dark Triad 'profiles' distinguished by trait prominence. Currently, neuroimaging studies have mainly concentrated on the neuroanatomy of individual dark traits, while the Dark Triad profile structure has been mostly overlooked. Filling this gap, we performed a clustering analysis of the Dirty Dozen Dark Triad questionnaire dividing 129 healthy subjects to two groups that were statistically different in each of the Dark Triad subscales. A further VBM analysis of the groups showed that a higher level of Dark Triad traits may manifest itself in decreased gray matter volumes in the areas related to emotional regulation (the dorsolateral prefrontal cortex, the cingulate cortex), as well as those included in the reward system (the ventral striatum, the orbitofrontal cortex). The obtained results shed light on the neurobiological basis underlying social interactions associated with the Dark Triad and its profiles.